Evaluation of non-point source pollution reduction by applying Best Management Practices using a SWAT model and QuickBird high resolution satellite imagery - Lee, MiSeon; Park, Geunae; Park, MinJi; Park, JongYoon; Lee, JiWan; Kim, SeongJoon (Journal of environmental sciences (China), 2010)
This study evaluated the reduction effect of non-point source pollution by applying best management practices （BMPs） to a 1.21 km^2 small agricultural watershed using a SWAT （Soil and Water Assessment Tool） model. Two meter QuickBird land use data were prepared for the watershed. The SWAT was calibrated and validated using dally streamflow and monthly water quality （total phosphorus （TP）, total nitrogen （TN）, and suspended solids （SS）） records from 1999 to 2000 and from 2001 to 2002. The average Nash and Sutcliffe model efficiency was 0.63 for the streamflow and the coefficients of determination were 0.88, 0.72, and 0.68 for SS, TN, and TP, respectively. Four BMP scenarios viz. the application of vegetation filter strip and riparian buffer system, the regulation of Universal Soil Loss Equation P factor, and the fertilizing control amount for crops were applied and analyzed.